COVID-19 pandemic resulted in more metastatic breast cancer cases at diagnosis - Roxana Pintican; Maria Magdalena Duma; Agostino Matteo Spada; Madalina Szep; Dan Eniu; Angelica Chiorean (Scientific Reports)
Abstract The study aimed to assess the impact of the COVID-19 pandemic on breast cancer diagnosis, tumor characteristics, and staging in an Eastern-European country. This retrospective study included 11,635 breast cancer patients and clients presenting between March 2019 and March 2022. Patients were categorized into pre-pandemic, pandemic, and post-pandemic groups. Data included age, sex, pathology, tumor characteristics (histologic type, grade, ER/PR/HER2 status), and TNM staging. Statistical analysis compared these parameters across the three-time intervals.During the pandemic, breast cancer diagnosis decreased significantly compared to the pre-pandemic period (9.1% vs. 13.17%, p < 0.001) but increased post-pandemic (11%, p = 0.013). Invasive ductal carcinoma of non-special type (IDC-NST) was predominant in all three-time periods. Aggressive tumors (Nottingham grade 3, ER negative) increased during the pandemic and post-pandemic times. Molecular subtypes showed variations across time intervals, with triple-negative tumors rising significantly. Larger tumors, increased lymph node involvement (9–19%), and distant metastasis characterized the pandemic and post-pandemic periods. Compared to pre-pandemic patients, post-pandemic ones were 7 times more likely to be metastatic at diagnosis (p < 0.05). The COVID-19 pandemic led to a significant decrease in breast cancer diagnosis, particularly during the pandemic period. Tumors appeared more aggressive, with higher lymph node and distant metastatic involvement. The long-term prognosis and healthcare cost implications remain uncertain. These findings emphasize the need for adapted cancer screening programs and healthcare system readiness during pandemics.COVID-19 pandemic has resulted in a lower detection rate among patients diagnosed with breast cancer and increased TNM stage.